PENINGKATKAN HASIL BELAJAR LEMPAR TURBO SISWA SECARA DARING DENGAN MENGGUNAKAN METODE RESITASI DI SD NEGERI 112 PALEMBANG - kristina, putri cicilia; Sukmadini, Irwan; AR, Nazom Nurhawi; Hidayatullah, Firdaus; Saputra, Ade Indra (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2023)
Classroom action research was conducted to improve the learning process which was not optimal during the covid 19 pandemic. The problems that occurred in schools and were often seen in students, especially in the PJOK subject matter of the basic motion of turbo throwing, namely the learning outcomes obtained by students were low, so this study aimed to improve the learning outcomes of throwing turbo using the recitation method in class IV.A students of SD Negeri 112 Palembang. Classroom action research was conducted in class IV.A of SD Negeri 112 Palembang with a total of 36 students. This research was conducted in two cycles. Based on the results obtained during the implementation of the pre-cycle class action research, cycle I and cycle II continued to increase. It is known that the results of the initial test, of the 36 students who were the object of this study, it turned out that only 8 students (22.2%) already had learning mastery, while the remaining 28 students (77.7%) did not have learning mastery. The results of the first cycle test showed that out of 36 students, 19 students (52.7%) had mastery learning, the remaining 17 students (47%) did not have mastery learning. The test results of the second cycle of 36 students, it turns out that 32 students (88.8%) already have learning mastery, only 4 students (11.1%) who do not have learning mastery. It can be concluded that the application of the recitation method to turbo throwing learning results in class IV.A students of SD Negeri 6 Palembang for the 2020/2021 academic year.